PENGARUH PEMANFAATAN LULUR SERUNI TERHADAP PERAWATAN KULIT TUBUH - Ningsih, Nuning Nila; Rahmiati, Rahmiati; Rosalina, Linda (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This article aims is to analyse the use of body scrub, wiping,Mustika Ratu against skin care body with frequency once a week,which is assessed in terms of smoothness and brightness of the skin ofthe body. This type of research is pre-experimental and only done onone group of experiments. The object of the research is the skin of thebody (hand skin). The population of the research were studentmajoring in sports and UNP Beauty and Makeup that has the samecriteria. Purposive sampling technique was used with carried outvolunteer amaunt to 5 people. Based on the results of its homogeneityand normality analysis, research data is normal and homogeneous.The hypothesis suggests that skin care body scrubs make use ofChrysanthemum in shows the significant on each indicators, Theresults t (count) 2.926 for smoothness and t (calculate) the brightnessto 2.714 > t (table) 2.022. The use of body scrub, wiping can smoothand brighten the skin of the body with the frequency once a week.Keywords: Utilization, chrysanthemums scrubs, skin care and